[tex]29) {3}^{ {x}^{2} - 2x + 5 } = 81[/tex]
[tex] {3}^{ {x}^{2} - 2x + 5 } = {3}^{4} [/tex]
[tex] {x}^{2} - 2x + 5 = 4[/tex]
[tex] {x}^{2} - 2x + 5 - 4 = 0[/tex]
[tex] {x}^{2} - 2x + 1 = 0[/tex]
[tex] {(x - 1)}^{2} = 0[/tex]
[tex]x - 1 = 0 = > x = 1 \: \in \: \mathbb{R}[/tex]
[tex]32) {2}^{ {x}^{2} + 3x + 4} = 4[/tex]
[tex] {2}^{ {x}^{2} + 3x + 4 } = {2}^{2} [/tex]
[tex] {x}^{2} + 3x + 4 = 2[/tex]
[tex] {x}^{2} + 3x + 4 - 2 = 0[/tex]
[tex] {x}^{2} + 3x + 2 = 0[/tex]
[tex] {x}^{2} + 2x + x + 2 = 0[/tex]
[tex]x(x + 2) + 1(x + 2) = 0[/tex]
[tex](x + 1)(x + 2) = 0[/tex]
[tex]x + 1 = 0 = > x = - 1\:\in\:\mathbb{R}[/tex]
[tex]x + 2 = 0 = > x = - 2\:\in\:\mathbb{R}[/tex]
[tex]34) {5}^{ {x}^{2} + 4x + 7 } = 625[/tex]
[tex] {5}^{ {x}^{2} + 4x + 7} = {5}^{4} [/tex]
[tex] {x}^{2} + 4x + 7 = 4[/tex]
[tex] {x}^{2} + 4x + 7 - 4 = 0[/tex]
[tex] {x}^{2} + 4x + 3 = 0[/tex]
[tex] {x}^{2} + 3x + x + 3 = 0[/tex]
[tex]x(x + 3) + 1(x + 3) = 0[/tex]
[tex](x + 1)(x + 3) = 0[/tex]
[tex]x + 1 = 0 = > x = - 1\:\in\:\mathbb{R}[/tex]
[tex]x + 3 = 0 = > x = - 3\:\in\:\mathbb{R}[/tex]